Engagement, motivation, and working performance - Bram Hadianto; Sabrina Wissen; Renate Severita Hapsariny; Shafira Putri Kurniawan; Yosephine Carolina (Integrated Journal of Business and Economics (IJBE), 2021)
This study aims to examine and analyze the effect of employee engagement and motivation on working performance. This population is 618 employees working at one of the textile companies in Bandung, distributed into seven divisions. The number of samples of 247, furthermore, is counted by the Isaac and Michael formula. Because of the divisions, the pieces are taken by a stratified random sampling technique. Ominously, not all of them are responsive. Hence, this research can get a 54.66% participating level on the online survey or successfully collect 135 responses. Besides, this study utilizes the confirmatory factor analysis and the composite reliability coefficient analysis to test data quality. After that, the structural equation model based on variance is used. After examining the proposed hypothesis and discussing the related facts, this study deduces that a positive effect of employee engagement and motivation on working performance exists.